Internal Function and Categories of Adverb Phrases in Tolitoli Language - Saputra, Nur Salim; Partiwi, Ririn; Rojuli, Safin (Sinergi International Journal of Education, 2025)
Tolitoli is a regional language spoken in Central Sulawesi, which still has a significant number of native speakers despite experiencing cultural fluctuations. Efforts are needed to protect and preserve this local language. This study aims to classify and describe adverbial phrases in the Tolitoli language using a qualitative descriptive method with observation, recording, and note-taking techniques. Data were collected from interviews with native speakers in Ginunggung Village, as well as relevant literature. The findings show that the dominant adverbial phrase patterns in Tolitoli are T-H-T (Modifier-Head-Modifier) and T-T-H (Modifier-Modifier-Head), with the modifier often appearing after the head, as seen in noosa laus (too slow). These phrases are categorized into three main types: manner, degree, and time, with degree adverbial phrases being the most dominant. Double modifiers are used to emphasize intensity or quality. These findings enhance our understanding of the syntax of the Tolitoli language and contribute to the knowledge of linguistic diversity in Indonesia.